Comparative Production Performances of Different Types of Quail (Coturnix coturnix japonica) (The Agriculturists, 2015)
A study was conducted with four types of quail named Japanese (J), White (W), Black (BL) and Brown (Br) quail in BLRI, Savar, Dhaka to understand their productive and reproductive performances. A total of 1953 day-old chicks of quails were produced in successive two hatches. The highest fertility and hatchability were observed in White (98.13%) and Japanese (73.20%) types compared to their counterparts. White quail was significantly better for egg weight and chick weight than other the three types. The 5th week body weights were 117.94 ± 10.70, 114.71 ± 11.13, 98.28±9.69 and 107.24±8.98 g, respectively for W, Br, J and Bl. Significantly higher body weight was found in W and Br followed by Bl and J quail at different ages. The total number of eggs upto 24th week of age was 81.23 ± 0.67, 83.05 ± 0.69, 90.52± 0.56, and 93.31 ± 1.05 respectively, for W, Br, J and Bl and these significantly (p